Unraveling the potential of graphene quantum dots against Mycobacterium tuberculosis infection - Santarelli, Giulia; Perini, Giordano; Salustri, Alessandro; Palucci, Ivana; Rosato, Roberto; Palmieri, Valentina; Iacovelli, Camilla; Bellesi, Silvia; Sali, Michela; Sanguinetti, Maurizio; De Spirito, Marco; Papi, Massimiliano; et al. (Frontiers in Microbiology, 2024)
The emergence and spread of drug-resistant Mycobacterium tuberculosis (Mtb) strains prompted the need to develop new drugs and therapeutic strategies. Carbon-based nanomaterials (CNMs), particularly graphene oxide (GO), have shown a promising anti-TB activity, thanks to their ability to entrap mycobacteria in the extracellular milieu and to stimulate ROS production. Unfortunately, GO showed a significant toxicity in human peripheral blood mononuclear cells (PBMCs). Graphene quantum dots (GQDs) have been demonstrated to have a high biocompatibility with eukaryotic cells. We investigated differently functionalized graphene quantum dots (non-functionalized, L-GQDs, aminated-, NH2-GQDs and carboxylated - COOH-GQDs) alone or in combination with isoniazid (INH), amikacin (AMK) and linezolid (LZD) against Mtb in both axenic cultures and in in vitro infection models. GQDs did not exhibit trapping activity nor direct mycobactericidal effects. On the contrary, co-administration of AMK with NH2-GQDs significantly reduced CFUs. While L-GQDs and COOH-GQDs alone did not show any significant anti-mycobacterial activity, NH2-GQDs treatment reduced CFUs when used in in vitro model. Additionally, NH2-GQDs and COOH-GQDs significantly increased AMK activity in infected macrophages. Our results suggest that GQDs may serve as a scaffold for the development of innovative anti-TB treatments.